Development of a partial discharge testing system for potential transformers - Prombud, T.; Kitcharoen, P.; Yutthagowith, P. (My University, 2018)
In this paper, the development of a partial discharge testing system for potential transformers (PTs) is presented. The system is composed of a low-voltage and 200-Hz power frequency converter connected with a low pass filter, a high-voltage transformer, and a conventional partial discharge detection system. The performances of the converter with three generated waveform, i.e. square wave, quasi-square wave, and unipolar pulse width modulation (PWM) are compared in terms of the DC charging voltage, the voltage difference (peak voltage/square root of 2 and rms voltage), total harmonic distortion of the output high voltage (THDv), and background noises in the partial discharge test. It is found that the unipolar PWM frequency converter provides the best performances in terms of the voltage difference, THDv, and background noise. The voltage difference and THDv are lower than 5%, and the background noise is less than 2.5 pC. In addition, the developed system has been used for the real partial test on a potential transformer in the distribution system successfully.
Keywords: Frequency converter; High-voltage tests; Partial discharge; Potential transformer; Power quality